The importance of parents' attention to complete aggressive behavior - Desep Pria Pandri; Netrawati Netrawati (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2022)
Aggressive behavior is an act that causes other people to experience suffering, which results in physical and psychological suffering. Aggression is caused by a lack of parental attention and high peer conformity. This study aims to analyze (1) student aggressiveness, parental attention and peer conformity, (2) the contribution of parental attention and peer conformity individually with quantitative methods of descriptive correlational research to see the relationship between the independent variables and the dependent variable. The population of this study were students of class VII, VIII, and IX of SMP Negeri 21 Padang who were registered in the odd semester of the 2021/2022 academic year as many as 374 students. The research sample was 193 students, the research sample was taken using purposive sampling technique. The findings of this study explained that parental attention and peer conformity contributed 42.1% to aggressive behavior. That is, parental attention and peer conformity are factors that contribute to reducing and reducing student aggressive behavior at SMP Negeri 21 Padang. This means that parental attention, peer conformity and aggressive behavior are greatly reduced. Meanwhile, in some aspects that are still in the moderate category in each research variable, it is necessary to improve through guidance and counseling services. The research data shows that the higher the attention of parents and the conformity of peers, the lower the aggressive behavior of students. The data of this study indicate that parental attention and peer conformity are higher. These data indicate the lower the aggressive behavior of students. In connection with the results of this study the authors can provide suggestions: 1) students can take advantage of guidance and counseling services to form positive behavior. 2) Guidance and Counseling Schools cooperate with school personnel, parents and students in preventing and reducing aggressive behavior and the principal as a leader must be able to assist guidance and counseling teachers in establishing good cooperation with parents and other school parties, so as to prevent and reduce aggressive behavior